A detailed review on biosynthesis of platinum nanoparticles (PtNPs), their potential antimicrobial and biomedical applications - Jan, Hasnain; Gul, Roby; Andleeb, Anisa; Ullah, Sana; Shah, Muzamil; Khanum, Mehnaz; Ullah, Imran; Hano, Christophe; Abbasi, Bilal Haider (Journal of Saudi Chemical Society, 2021)
[Display omitted] Platinum nanoparticles (PtNPs) are an attractive candidate for application in many areas of biotechnology, nanomedicine, and pharmacology, owing to their large surface area and biological properties. Different approaches, including physical, chemical, and biological (plants, bacteria, algae, and fungi) are presently being used for synthesis of PtNPs. However, these conventional methods (physical and chemical) present potential threat to health and environment because of the use of harsh chemicals and hazardous reaction conditions, except biological synthesis means which are substantially considered ecofriendly, economic and non-toxic. PtNPs are extensively studied due to their potent physicochemical and biological properties including antioxidant, antimicrobial and anticancer properties. This review offers a comprehensive assessment of the current knowledge about the synthesis of PtNPs using physical, chemical, and biological (plants, bacteria, algae, and fungi) approaches and their potential antimicrobial and biomedical applications especially in cancer and photothermal therapy. Interestingly, this review highlights role of PtNPs as nano-diagnostic and nanomedicine. Furthermore, nanotoxicity related to PtNPs, as well as the future prospects and opportunities of PtNPs based nano-therapeutics are also discussed. Overall, the emerging potential biological applications of PtNPs makes it viable to foresee their more promising outcomes in biomedical field in the upcoming future.